Anaerobic treatment of pharmaceutical waste fermentation broth - Zupančič, Gregor Drago (Array, 2009)
Summary: The feasibility of anaerobic co-digestion of pharmaceutical waste fermentation broth (spent mycelia) mixed with pig slurry and corn-grass silage was studied. The waste broth proved very toxic to luminescent bacteria Vibrio fischeri (30 min EC50 = 1.19–3.35 vol. %) while it expressed lower toxicity to activated sludge (180 min EC50 = 4.11–15.32 vol. %). Initially, stabilization studies in aerobic and anaerobic conditions were performed to confirm feasibility of anaerobic degradation. A 30 L conventional mesophilic reactor was used for further digestion experiments. The control experiment (pig slurry and corn-grass silage only) with OLR of 1.5 kg m–3 d–1 achieved 70 % COD removal and methane production of 25.4 L d–1. The first experiment with added fermentation broth (OLR of 1.8 kg m–3 d–1) achieved 79 % COD removal and good methane production (30.9 L d–1). The second experiment with more fermentation broth (OLR of 2.2 kg m–3 d–1) failed after 20 days, but the system recovered when the OLR was reduced to 2.0 kg m–3 d–1. In the third experiment only pharmaceutical broth was used as a substrate. The process failed after 10 days of operation due to toxic shock. It has been concluded that the toxic impact could be avoided with an OLR not higher than 2.0 kg m–3 d–1, but at the same time pharmaceutical broth must not contribute more than 25 % to the total OLR